Miscousing–Wisconsin - Frederic G. Cassidy (Names, 1991)
Abstract The name Wisconsin, never satisfactorily explained, was first recorded as Miscousing. Was this form due to dialect variation in Indian sources, to mishearing by early recorders, or to some other cause? Another suggestion is that the M- form could have been an echo of an easterly name, Miscou, well known to French navigators.